2020
DOI: 10.1016/j.jbankfin.2020.105902
|View full text |Cite
|
Sign up to set email alerts
|

Fear of hazards in commodity futures markets

Abstract: We examine the commodity futures pricing role of active attention to weather, disease, geopolitical or economic threats or "hazard fear" as proxied by the volume of internet searches by 149 query terms. A long-short portfolio strategy that sorts the cross-section of commodity futures contracts according to a hazard fear signal captures a significant premium. This commodity hazard fear premium reflects compensation for extant fundamental, tail, volatility and liquidity risks factors, but it is not subsumed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 71 publications
(122 reference statements)
1
16
0
Order By: Relevance
“…The impact of COVID-19 and other global pandemics (SARS, H1N1 virus, and EVD) is mainly because the global health crises and events usually produce strong fears and anxieties ( Chen, Jang, & Kim, 2007 ). Generally, fear is one of a set of basic or innate human moods or emotions that is linked to irrationality ( Fernandez-Perez, Fuertes, Gonzales-Fernandez, & Miffre, 2020 ; Goetzmann, Kim, & Wang, 2015 ). 1 Investors misattribute fear as information when making investment judgements and decisions ( Schwarz & Clore, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of COVID-19 and other global pandemics (SARS, H1N1 virus, and EVD) is mainly because the global health crises and events usually produce strong fears and anxieties ( Chen, Jang, & Kim, 2007 ). Generally, fear is one of a set of basic or innate human moods or emotions that is linked to irrationality ( Fernandez-Perez, Fuertes, Gonzales-Fernandez, & Miffre, 2020 ; Goetzmann, Kim, & Wang, 2015 ). 1 Investors misattribute fear as information when making investment judgements and decisions ( Schwarz & Clore, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Goetzmann et al (2015) utilize weather-induced mood and investigate the impact on U.S. institutional investors. Fernandez-Perez et al (2020) evaluate the role of “hazard fear” in commodity futures pricing. However, measures of fear induced by specific events, such as the global health crisis, are quite limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Textual analysis has been widely applied in the finance literature to study the impact of text-based information on stock returns (e.g., Loughran & McDonald, 2011;Tetlock et al, 2008) demonstrating that it represents an efficient alternative to capture relevant sources of information. Other authors such as Fernandez-Perez et al (2020) concluded that text-based measures (in their work, google trends) account for the futures price variation observed in the market.…”
Section: The Publication Variablementioning
confidence: 99%
“…Gao and Süss (2015) find that proxies of investor sentiment can also predict commodity futures returns at cross-sectional level. Fernandez-Perez et al (2020) investigate how fear of Hazards can explain the cross-sectional commodity prices based on data from January 2005 to December 2018. However, so far, there has been scant literature investigating how rare disaster concerns predict commodity returns in the time series.…”
Section: Literaturementioning
confidence: 99%